Życie konsekrowane między proroctwem a eschatologią - Kijas, Zdzisław Józef (Studia Pastoralne, 2020)
In the religious life two big charisms are important around which all the others, that I would call minor, subsidiary or accompanying ones, are situated. What I have in mind are the charisms of prophecy and industriousness. The most important calling of a religious person is to testify about the presence of God as experienced “here and now”, which is similar to the calling of a prophet. His/her task is to get as close to God as possible and look at the world from God’s perspective. A prophet, like a religious person, is not given a gift of meeting God face to face, does not have insight into the heart of divine matters, but rather is able to see the world with God’s eyes and makes His point of view available. From this moment, on a religious person is speaking “on behalf” of God and sees everything from His perspective. This charism is coupled with the charism of industriousness, for getting close to God and to people is an effort, a constant struggle to overcome difficulties, both internal and external ones, of spiritual and carnal nature. An institute a religious person belongs to is, or should be, helpful in this process. The same applies to his/her entire life, his/her difficulties and joys. That is because the most important vocation of a religious person is to try to make God visible in his/her life in the world, so that His word might be heard and His will be done.